Transparansi dan Akuntabilitas Tata Kelola Pemerintahan Daerah - Hendrich Juk Abeth; Adi Wijaya; Gunawan Steffan Ikkyu B; Abdul Rauf (LPPM STIH Awang Long, 2020)
This study aims to analyze the transparency of local governance, as well as to analyze the accountability of local governance. This research is a normative study, using a statutory approach, a conceptual approach, and a historical approach, the data used are primary and secondary legal materials, all data collected were analyzed qualitatively. The results show that in order to achieve the goal of regional autonomy, good government governance is needed. In line with the realization of justice and prosperity of the people according to the ideals of the 1945 Constitution, good government governance has three main components, namely: the government (state), the private sector or the business world (private sector) and society (society). These three main components have their respective roles in creating good government governance. The role of the government sector is more dominant as policy maker, control and supervision. The private sector is more of a driving force for activity in the economic sector. The public sector is more of an object as well as a subject in a field that is driven by the government and private sectors.